Limits of interference with the intimacy of the man. Part I - Wardak, Zbigniew (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
In the article, there were discussed selected problems associated with the criminalization of such behaviours as: prostitution, incest, child sexual abuse. The article also dealt with protection of aggrieved parties in criminal proceedings through restrictions as for the openness.